God's new Israel : religious interpretations of American destiny - Cherry, Conrad, 1937- (University of North Carolina Press, 1998)
The belief that America has been providentially chosen for aspecial destiny has deep roots in the country's past. As both astimulus of creative American energy and a source of Americanself-righteousness, this notion has long served as a motivatingnational mythology. God's New Israel is a collection of thirty-one readings that trace the theme of American destiny under God through major developments in U.S. history. First published in 1971 and now thoroughly updated to reflect contemporary events, it features the words of such prominent and diverse Americans.